2012
DOI: 10.1126/scitranslmed.3003771
|View full text |Cite
|
Sign up to set email alerts
|

A Human Stem Cell Model of Early Alzheimer’s Disease Pathology in Down Syndrome

Abstract: Human cellular models of Alzheimer's disease (AD) pathogenesis would enable the investigation of candidate pathogenic mechanisms in AD and the testing and developing of new therapeutic strategies. We report the development of AD pathologies in cortical neurons generated from human induced pluripotent stem (iPS) cells derived from patients with Down syndrome. Adults with Down syndrome (caused by trisomy of chromosome 21) develop early-onset Alzheimer's disease, probably due to increased expression of the amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
232
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(246 citation statements)
references
References 37 publications
7
232
0
3
Order By: Relevance
“…However, increased levels of soluble Aβ 42 are found in ~50% of trisomy 21 fetal brains 118 , suggesting that APP may be dosage sensitive during fetal development of individuals with DS but that this change may not be sufficient to cause extensive Aβ deposition in the developing brain -perhaps because of efficient clearance. Consistent with this, overexpression of APP and/or increased levels of Aβ have been reported in trisomy 21 human cell models, including in induced pluripotent stem cells (iPSCs) derived from infants or young adults with DS [119][120][121][122] . Although triplication of APP does not necessarily lead to enhanced expression of APP and subsequent increase in Aβ accumulation in all contexts, overexpression of APP is strongly linked to Aβ deposition in adult life.…”
Section: Triplication Of Appmentioning
confidence: 65%
See 2 more Smart Citations
“…However, increased levels of soluble Aβ 42 are found in ~50% of trisomy 21 fetal brains 118 , suggesting that APP may be dosage sensitive during fetal development of individuals with DS but that this change may not be sufficient to cause extensive Aβ deposition in the developing brain -perhaps because of efficient clearance. Consistent with this, overexpression of APP and/or increased levels of Aβ have been reported in trisomy 21 human cell models, including in induced pluripotent stem cells (iPSCs) derived from infants or young adults with DS [119][120][121][122] . Although triplication of APP does not necessarily lead to enhanced expression of APP and subsequent increase in Aβ accumulation in all contexts, overexpression of APP is strongly linked to Aβ deposition in adult life.…”
Section: Triplication Of Appmentioning
confidence: 65%
“…Several genes involved in neurodevelopment have been suggested to have an important role in AD (including components of the WNT and reelin signalling pathway 201,202 ). Additionally, cultures of cells derived from infants with Down syndrome (DS) show clear overexpression of amyloid precursor protein (APP) [119][120][121][122] , and amyloid-β (Aβ) plaques have been found in the brains of children with DS who are as young as 8 years of age 65 . Thus, the syndrome offers a longitudinal perspective on the multilevel effects of Aβ and tau pathology during development.…”
Section: Identifying Risk and Protective Factors For Ad In Young Chilmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that, although many neuronal characteristics appear normal, Ts21 iPSCderived neurons display a significant synaptic deficit that is present in both glutamatergic and GABAergic subtypes. Recently, the work by Shi et al (57) reported "normal" synaptic activity in glutamatergic neurons differentiated from a single Ts21 iPSC line. However, the absence of GABAergic neurons in their system and diminutive excitatory synaptic currents (<5 pA) suggest aberrant network formation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genetic and epigenetic variability among patients may influence pharmacological responsiveness [45]. Disease modeling using iPS cells for AD has been actively pursued recently and has shown that pharmacological assays can be readily performed using these models [46][47][48][49][50][51][52]. Modeling and screening using glial-neuron coculture and 3-dimensional cultures, both of which better resemble in vivo physiological states, should also be pursued [53,54].…”
Section: Phenotypic Approachesmentioning
confidence: 99%